ANALYSIS OF THE INFLUENCE OF CAR, DPK AND PRODUCTIVE ASSETS QUALITY ON PROFITABILITY (ROA) WITH FDR AS AN INTERVENING VARIABLE MAQASHID AL NAJJAR'S PERSPECTIVE ON SHARIA BANK IN INDONESIA - Kusumastuti, Lely; Aziz, Abdul (UIN Mataram, 2023)
This research aims to answer the influence of CAR, DPK and KAP (Productive Asset Quality)on Profitability (ROA) with FDR as an intervening variable from Maqashid Al Najjar's perspectiveon Islamic banks in Indonesia. Data collection was carried out using documentation methods,library methods and documentation methods. In this research the author used quantitativemethods. In the following research, the population is all Sharia Commercial Banks and ShariaBusiness Units. Sampling used the purposive sampling method using certain criteria. From the resultsof the data analysis carried out, it shows that 1. The CAR variable has a positive effect on ROA,2. The DPK variable has no positive effect on ROA, 3. The KAP variable has no positive effecton ROA, 4. The FDR variable has no positive effect on ROA, 5. The variable CAR has nopositive effect on FDR, 6. The TPF variable has a positive effect on FDR, 7. The KAP variablehas no positive effect on ROA, 8. The FDR variable cannot mediate CAR on ROA, 9. TheFDR variable cannot mediate DPK on ROA, 10. The FDR variable cannot mediate KAP onROA